2010
DOI: 10.1253/circj.cj-09-0935
|View full text |Cite
|
Sign up to set email alerts
|

V-Shaped Trough in Autonomic Activity Is a Possible Precursor of Life-Threatening Cardiac Events

Abstract: Background:No reliable precursor of sudden cardiac death is known. Methods and Results:Holter electrocardiograms of 34 patients experiencing a cardiac event (event group, 20 deaths) were compared with 191 controls (no event group). The event group included 25 patients with ventricular fibrillation or acute myocardial infarction (AMI), and 9 with cardiac arrest due to complete atrioventricular block. The logarithms were calculated of the moving average of 5 successive values for the low-frequency component (LF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Our system will open doors to new strategies to minimize driver's risk by making available the relevant data during the actual process of driving. We reported that a V-shaped trough in autonomic activity is a possible precursor of life-threatening cardiac events (Osaka et al, 2010). The V-trough including the small variations that precede it spans approximately 190 minutes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our system will open doors to new strategies to minimize driver's risk by making available the relevant data during the actual process of driving. We reported that a V-shaped trough in autonomic activity is a possible precursor of life-threatening cardiac events (Osaka et al, 2010). The V-trough including the small variations that precede it spans approximately 190 minutes.…”
Section: Resultsmentioning
confidence: 96%
“…We aimed at finding a consistent precursor of a lethal cardiac event by examining Holter recordings in which such a spontaneous event was recorded. Holter recordings of 34 patients experiencing a cardiac event (Event-group, 20 deaths) were compared with 191 controls (NoEvent-group) (Osaka et al, 2010). The Event-group included 25 patients with ventricular fibrillation or acute myocardial infarction, and 9 with cardiac arrest due to complete atrioventricular block.…”
Section: V-shaped Trough In Autonomic Activity As a Possible Precursormentioning
confidence: 99%
“…Neuroautonomic changes were assessed by the authors using spectral analysis of R-R intervals obtained from Holter electrocardiograms. A sudden switch from parasympathetic activation into sympathetic activation resulted in AMI or VF in 22 of 34 patients whereas nine patients developed AV block during a switch from sympathetic to parasympathetic activation (Osaka et al 2010).…”
Section: Neuroautonomic Dysbalance During Early In-hospital Carementioning
confidence: 97%
“…The V-trough was marked by a small variation lasting 2 hours, an abrupt descent lasting 30 minutes, and a sharp ascent for 40 minutes. The criteria for a V-trough were defined mathematically to automatically determine if a V-trough has occured 23 . The sensitivity and specificity of an LF/HF Vtrough for predicting ventricular fibrillation are 87% and 95%, respectively.…”
Section: Precursor Of Scdmentioning
confidence: 99%